Bike-sharing: Its history, models of provision, and future. [Vortrag auf der Velo-city 2009 Konferenz vom 12. -15. Mai 2009 in Brüssel.] - DeMaio, Paul (My University, 2009)
This paper briefly discusses the history of bike-sharing from the early 1st generation program to present day 3rd generation programs. There is a detailed examination of models of provision and the state of the art outside of the European Union. The paper concludes with looking into the future of bike-sharing, with a discussion about what a 4th generation program could be.
Keywords: Fahrradverkehr; Mobilität; Nahverkehr; Entwicklungstendenz; Individualverkehr; Fahrradgeschichte; Fahrradförderung; Bereitstellung; Bike-Sharing; Öffentliches Fahrradverleihsystem